20 lat trzeciego sektora w Polsce – doświadczenia i perspektywy - Cieślik, Łukasz (Przegląd Politologiczny, 2018)
Year 1989 marked a breakthrough in the presence and development of non-governmental organizations (NGOs) in Poland. The freedom of association was restored, and the society immediately took advantage of this freedom. Since the early 1990s, decentralization has been coupled with a revived activity of the civic sector, and a clear increase in the number of ‘grass-root’ initiatives, stimulated by the society itself. The number of NGOs has kept growing, including the associations, foundations, and church organizations. The scope of their activity, the number of employees and the tasks they undertake have been expanding. In order to understand the essence of social economy, and primarily to notice the opportunity to develop the state on the basis of the principles of social economy, it was necessary to change the definition of the essence of the state and society, their role, and to correlate their mutual objectives and needs. The administrative reform executed in Poland in 1999, resulted in moving the burden of public tasks from the central government to the units of territorial self-government. The administrative reform introduced three layers of territorial division in order to promote self-governance, facilitate the operation of local authorities, and bring them closer to citizens. Over the last twenty years, NGOs have become a valuable partner in territorial self-government by performing various kinds of public tasks and thus becoming an exceptionally significant element of social policy. The principles regulating the co-existence of the third sector and the state are laid down in the act of law of April 24, 2003 on public benefit and volunteer work, which provides a comprehensive regulation of the activity of NGOs in the realm of public life, the principles (subsidiarity, sovereignty of parties, partnership, efficiency, fair competition, and transparency), and the form of cooperation between such organizations and the organs of public administration with respect to the performance of public tasks. It should be emphasized, however, that while NGOs have taken over services rendered in some areas, their potential has not been fully utilized. The functioning of social organizations manifests civic freedom and society’s self-organization. The activities of the third sector organizations allow the fulfillment of important social needs, such as the need for spontaneous association, social initiative and organizational autonomy. The functioning of social organizations has an advantageous influence on the activity of public and private organizations. The NGOs in Poland and abroad play an increasingly significant role, both in the development of civic society of democratic states, and also in the process of performing public tasks and the development of economies. At present, forms of cooperation between NGOs and the territorial self-government are being sought. This may indicate that both local authorities and the third sector organizations have reached a point where they are ready to form a real partnership. This is an optimistic statement, especially given the opportunity to develop the sector of social economy using the financial means of the EU structural funds. Along with the ageing of affluent societies, social exclusion, poverty and unemployment are the fundamental social problems for Poland and the whole of modern Europe. The subjects of the third sector of an economy can play a key role in solving these problems.